Disquieting uncertainty. Three glimpses into the future - Volker H. Schmidt (European Journal of Futures Research, 2017)
Abstract The article sketches three major realms - the realm of world order, the realm of work, and the realm of social policy - that will in all likelihood undergo fundamental change in the years and decades ahead, raising deeply unsettling questions about their future. The account is framed by the concept of global modernity, which, while not spelled out in detail, guides the presentation of data and other secondary materials in the aim to demonstrate connections between, and, at least to some extent, common roots of, phenomena and developments that might otherwise appear to be quite disparate. The author does not present any solutions for the problems and challenges discussed in the article, but hopes to sensitize readers to their urgency and to stimulate fruitful ideas for what will ultimately have to be a collective endeavor involving not only scholars from around the world but also the general public.